Development e-module on human reproduction system materials science-Islam integrated to improve science literacy and student learning outcomes - Siti Aisyah Firdani; Abdul Gofur; Betty Lukiati (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Low scientific literacy is due to the large amount of material being taught and not applying basic biological concepts to problems commonly encountered in the surrounding environment. The Islamic science integration approach, which was developed into teaching materials in the form of e-modules, needs to be applied because it places a variety of diversity in scientific disciplines (Islamist studies, Natural studies, Social studies, and Humanities). The research aims to develop and test an E-module's validity, practicality, and effectiveness based on Problem-Based Learning (PBL) Integrated Islamic Science Human Reproductive System Material to Improve Science Literacy and Student Learning Outcomes. The research and development model refers to a Branch consisting of ADDIE, namely the analyze, design, develop, implement, and evaluate stages. The data collection techniques used were questionnaires and validation sheets. The results of research on the effectiveness of e-modules show that e-modules are very valid in improving scientific literacy and student learning outcomes. Based on the N-gain calculation, scientific literacy is in the medium category with significant t-test results. The learning outcomes are in the high category with very significant t-test results. This research shows that the PBL-based e-module material on the science-Islam integrated human reproductive system can be developed and effectively used in learning activities.Abstrak. Literasi sains rendah disebabkan banyaknya materi yang diajarkan, kurang menerapkan konsep dasar biologi terhadap permasalah yang biasa ditemui di lingkungan sekitar. Pendekatan integrasi sains-Islam yang dikembangkan menjadi bahan ajar berupa e-module perlu diterapkan karena menempatkan berbagai keberagaman terhadap disiplin ilmu (Islamis-Studies, Natural studies, Social studies dan Humaniora). Penelitian bertujuan untuk mengembangkan, menguji kevalidan, kepraktisan, dan keefektifan e-module berbasis Problem Based learning (PBL) Materi Sistem Reproduksi Manusia Terintegrasi Sains Islam untuk Meningkatkan Literasi Sains dan Hasil Belajar Mahasiswa. Model penelitian dan pengembangan mengacu pada Branch terdiri dari ADDIE yaitu tahap analyze, design, develop, implement, dan evaluate. Tenik pengumpulan data yang digunakan berupa angket dan lembar validasi. Hasil penelitian terhadap keefektifan e-module menunjukkan bahwa e-module sangat valid dalam meningkatkan literasi sains dan hasil belajar mahasiswa. Berdasarkan perhitungan N-gain literasi sains masuk kategori sedang, dan hasil belajar masuk kategori tinggi dengan hasil uji-t yang sangat signifikan. Hasil penelitian ini dapat disimpulkan bahwa e-module berbasis PBL materi sistem reproduksi manusia terintegrasi sains-Islam dapat dikembangkan dan efektif digunakan dalam kegiatan pembelajaran.